A Dosimetric Comparison of IMRT Vsvmat Techniques in Single Vocal Cord Irradiation in The Treatment of T1an0 Glottic Cancer - Mortada Elsharief, Mohamed; Hassouna, Ashraf Hamed; Shouman, Tarek; Elbadraway, Amr; Mosallam, Abdelrahman; Abdelfatah, Sherweif Mohamed (Journal of Neonatal Surgery, 2025)
This dosimetric study compares intensity-modulated radiotherapy (IMRT) and volumetric-modulated arc therapy (VMAT) techniques in single vocal cord irradiation (SVCI) for patients with T1aN0 glottic cancer. Historically, early glottic carcinoma has been managed with large-field radiotherapy, often exposing surrounding healthy tissues to unnecessary radiation and increasing the risk of complications. In contrast, SVCI, inspired by the precision of surgical laser excision, targets only the affected vocal cord, minimizing radiation exposure to adjacent structures. Ten patients underwent CT simulation and treatment planning with both 7-field IMRT and single-arc VMAT. Dose-volume histogram analyses were performed to evaluate planning target volume (PTV) coverage, homogeneity index (HI), conformity index (CI), and dose exposure to organs at risk (OARs). Results demonstrated comparable PTV coverage between IMRT and VMAT, with VMAT showing statistically superior HI and CI. No significant differences were observed in radiation doses delivered to critical OARs including the contralateral vocal cord, pharyngeal constrictor muscles, thyroid gland, carotid arteries, and spinal cord. These findings affirm the feasibility of SVCI using either technique, with VMAT offering dosimetric advantages in homogeneity and conformity. This study supports the use of advanced radiotherapy techniques to achieve effective and safer treatment of early-stage glottic cancer.